Sportswashing or Strategic Branding? The Saudi Pro League's Role in Reshaping Global Perceptions of Saudi Arabia - Imam Ansori; Muhammad Yamin; Arif Darmawan; Soni Martin Anwar (Universitas Warmadewa, 2025)
This study analyzes the change of the Saudi Pro League (SPL) from 2021 to 2024, assessing whether these initiatives represent sportswashing or authentic nation branding. Since 2021, Saudi Arabia has allocated billions into the acquisition of international football talents and the enhancement of facilities, notwithstanding global condemnation of its human rights record. This research utilizes Anholt's nation branding hexagon framework and adopts a qualitative case study technique with comparative aspects, incorporating official documents, public opinion surveys, media content analysis, and tourism statistics. Findings indicate a multifaceted